Pengembangan Model Kinerja Karyawan berdasarkan Karir, Spiritual Capital, dan Disiplin - Prasodjo, Imam; Hardianto, Ade Manggala; Faujiah, Faujiah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: The purpose of this research is to develop a model of employee performance involving career, organizational spirituality, and discipline. Method: The research method is a survey method by distributing questionnaires to 150 employees and using the SEM (structural equation modeling) analysis tool. researchers distributed questionnaires via gGoogleform, and classify, and analyze the model. Result: The findings of the outer model research show that all indicators are valid, and the hypothesis test is accepted as significant. Career variables and organizational spirituality have a direct effect on discipline, namely 0.260 and 0.689. While career and organizational spiritual variables have a direct effect on employee performance of 0.233 and 0.435. Career and spiritual mediation and employee discipline have a direct effect of 0.187, 0.230 ,and 0.334. Limitation: Research limitations. Researchers limit the survey area to only the city of Cilegon, so it is necessary to invade the research object in order to produce a more established model. Novelty: The novelty of the research is involving organizational spirituality as another perception to increase sales.